SAYA, JO, DAN OO’O DALAM PERSFEKTIF KESOPANAN MASYARAKAT GORONTALO - Muh. Lukman Hakim (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Research of Gorontalo language in general has been conducted since 1914. Recently, hundreds of Research have been done. Almost all aspects of Gorontalo language has been examined. However, the study of Gorontalo language relation to other languages   are still rare. Therefore, this paper will describe the changes in the meaning of vocabulary uptake of Manado Malay and Indonesian language into Gorontalo relation to politeness, social relationships, and gender. The method used in this paper is a descriptive qualitative analysis with special sampling techniques in accordance with the purpose of writing (purposive sampling).